State-owned asset management reform and corporate cash holdings: Study on central enterprise income distribution policy - Shangkun Liang; Qing Dong; Shuwei Sun (China Journal of Accounting Studies (CJAS), 2022)
Based on the data of A-share listed central state-owned enterprises (CSOEs) and non-state-owned listed companies in China from 2003 to 2019, we use propensity score matching and the difference-in-difference method to examine the impact of CSOEs' income distribution policy on corporate cash holding decisions. The results show that the policy implementation improves corporate cash holding levels. Further analysis found that: (1) corporate financial flexibility can alleviate the policy effect; (2) when the control distance is shorter, and environmental uncertainty is higher, the policy effect is stronger; and (3) the policy has a lagged effect. This study theoretically expands the research on the economic consequences of income distribution policy and the influencing factors of cash holdings. It further aids policymakers in improving the state-owned capital gains distribution system, deepening the reform of state-owned enterprises, and providing empirical evidence at firm level for investors to understand the real impact of the policy.
Keywords: 650; Income distribution; cash holdings; cash flow constraints; financial flexibility